Prospective Monitoring Reveals Dynamic Levels of T Cell Immunity to Mycobacterium Tuberculosis in HIV Infected Individuals - Mitchell, Jessica E. (Public Library of Science, 2012)
Monitoring of latent Mycobacterium tuberculosis infection may prevent disease. We tested an ESAT-6 and CFP-10-specific IFN-γ Elispot assay (RD1-Elispot) on 163 HIV-infected individuals living in a TB-endemic setting. An RD1-Elispot was performed every 3 months for a period of 3–21 months. 62% of RD1-Elispot negative individuals were positive by cultured Elispot. Fluctuations in T cell response were observed with rates of change ranging from −150 to +153 spot-forming cells (SFC)/200,000 PBMC in a 3-month period. To validate these responses we used an RD1-specific real time quantitative PCR assay for monokine-induced by IFN-γ (MIG) and IFN-γ inducible protein-10 (IP10) (MIG: r = 0.6527, p = 0.0114; IP-10: r = 0.6967, p = 0.0056; IP-10+MIG: r = 0.7055, p = 0.0048). During follow-up 30 individuals were placed on ARVs and 4 progressed to active TB. Fluctuations in SFC did not correlate with CD4 count, viral load, treatment initiation, or progression to active TB. The RD1-Elispot appears to have limited value in this setting.